High-resolution tracking of single-molecule diffusion in membranes by confocalized and spatially differentiated fluorescence photon stream recording. - Sahl, S; Leutenegger, M; Hell, S; Eggeling, C (2014)
The performance of a method is assessed which allows for the spatiotemporal tracking of single dye-labeled molecules during two-dimensional (2D) diffusional transits through the focal area of a modified confocal microscope. In addition to facilitating the observation of molecular diffusion paths at the shot-noise limit of bright organic emitters with spatial and temporal precisions of ∼10-20 nm and <0.5 ms, respectively, the direct access to the complete stream of detected photons is beneficial for characterizing nanoscale details such as transient pausing (binding). We discuss technical aspects of this approach, along with results from its application to measuring lipid membrane dynamics in live mammalian cells. Presented topics include a discussion of the advantages of the single-photon collection mode and instrument as well as computational considerations for the localization process. A proof-of-principle experiment shows that optical nanoscopy by stochastic single-molecule switching and position readout could be implementable in parallel with such fast molecular tracking. This would allow direct access to contextual imaging data of local cytoskeletal structural elements or localized longer-lived protein assemblies.